The distinctive role of menthol in pain and analgesia: Mechanisms, practices, and advances - Li, Ziping; Zhang, Haoyue; Wang, Yigang; Li, Yize; Li, Qing; Zhang, Linlin (Frontiers in Molecular Neuroscience, 2022)
Menthol is an important flavoring additive that triggers a cooling sensation. Under physiological condition, low to moderate concentrations of menthol activate transient receptor potential cation channel subfamily M member 8 (TRPM8) in the primary nociceptors, such as dorsal root ganglion (DRG) and trigeminal ganglion, generating a cooling sensation, whereas menthol at higher concentration could induce cold allodynia, and cold hyperalgesia mediated by TRPM8 sensitization. In addition, the paradoxical irritating properties of high concentrations of menthol is associated with its activation of transient receptor potential cation channel subfamily A member 1 (TRPA1). Under pathological situation, menthol activates TRPM8 to attenuate mechanical allodynia and thermal hyperalgesia following nerve injury or chemical stimuli. Recent reports have recapitulated the requirement of central group II/III metabotropic glutamate receptors (mGluR) with endogenous κ-opioid signaling pathways for menthol analgesia. Additionally, blockage of sodium channels and calcium influx is a determinant step after menthol exposure, suggesting the possibility of menthol for pain management. In this review, we will also discuss and summarize the advances in menthol-related drugs for pathological pain treatment in clinical trials, especially in neuropathic pain, musculoskeletal pain, cancer pain and postoperative pain, with the aim to find the promising therapeutic candidates for the resolution of pain to better manage patients with pain in clinics.